Optimization of bio-protein production from banana peels by sequential solid state bioconversion - Saheed, Olorunnisola Kola; Jamal, Parveen; Alam, Md. Zahangir (2012)
Bio-protein is one of the products of biotechnology innovation which is a promising substitute for conventional human and animal feed supplement. In order to develop optimum media parameters for bio-protein from banana peels (BP), solid sate bioconversion (SSB) involving fungal and yeast systems was performed. Single factor optimization result showed that bio-protein synthesis was optimum at day 6 while KCl (0.5%), sucrose (5%), MgSO4.7H2O (0.4%), NH4H2PO4 (0.6%) and solid content (5.5%) respectively were needed. Optimum level for sucrose and NH4H2PO4 was (5%, 0.6%), sucrose and MgSO4.7H2O gave (5%, 0.4%) while MgSO4.7H2O and NH4H2PO4 levels were 0.4% and 0.6%. Face centered central composite design (FCCCD) gave a significant model which suggested 4.79% for sucrose, 0.44% MgSO4.7H2O and 0.61% NH4H2PO4. Validation of the model gave 143.18 mg/g bio-protein which was about 31.2% more than predicted value.